6a+6=8a

Simple and best practice solution for 6a+6=8a equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6a+6=8a equation:


Simplifying
6a + 6 = 8a

Reorder the terms:
6 + 6a = 8a

Solving
6 + 6a = 8a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-8a' to each side of the equation.
6 + 6a + -8a = 8a + -8a

Combine like terms: 6a + -8a = -2a
6 + -2a = 8a + -8a

Combine like terms: 8a + -8a = 0
6 + -2a = 0

Add '-6' to each side of the equation.
6 + -6 + -2a = 0 + -6

Combine like terms: 6 + -6 = 0
0 + -2a = 0 + -6
-2a = 0 + -6

Combine like terms: 0 + -6 = -6
-2a = -6

Divide each side by '-2'.
a = 3

Simplifying
a = 3

See similar equations:

| x+2y-5=28 | | x^4-7x^2=10 | | -2+(-1)+6=x | | 0.95x+0.05(20-x)=0.10(-116) | | x+(0.35*(100-x))=81 | | 7q-(3q+10)=5-(4q-4) | | 6(5x-6)=-3 | | 5(x-25)= | | ax+b=-c | | 6x+1=21 | | 15x-9=6x-2 | | 0.4x-2.8=1.4x+1.8 | | 8(a+b)-3b+12= | | 16t^2-9= | | 12y/3=18 | | -(u+3)+3u= | | 3.9+10m=8.35 | | 2(4-x)-3(1+3x)=16 | | 5(2x+3)-5=65 | | 0.50x+0.35(30)=49.5 | | -2.7-2.7=-2.1x-2.1 | | (15x/3)=47 | | 4q-(7q+10)=6-(5q-5) | | n-8=21 | | (2X+3)(5X+4)=20 | | 7x-9=-9x-7 | | 2-3(x-7)=1 | | 6(n-6)+7n=-140 | | x^1/3=4/3 | | 8x=-3+1 | | 2000+100h=1800+150h | | 1100+800+4z=700+300+7z |

Equations solver categories